2020
DOI: 10.21203/rs.3.rs-71611/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive values of neutrophil-to-lymphocyte ratio on disease severity and mortality in COVID-19 patients: a systematic review and meta-analysis

Abstract: Background:Coronavirus disease 2019 (COVID-19), a highly infectious disease, has been rapidly spreading all over the world and posted a great threat to global public health. Patients diagnosed with severe or critical cases have a poor prognosis. Hence, it is crucial for us to identify potential severe or critical cases early, and give timely treatments for the targeted patients. In the clinical practice of treating COVID-19 patients, we have observed that the neutrophil-to-lymphocyte ratio (NLR) of severe pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 39 publications
6
38
3
Order By: Relevance
“…12 A metanalysis done by Xiaoming et al to evaluate the predictive value of NL ratio suggested that NL ratio has good predictive in terms of severity and mortality in COVID-19 hence helping clinicians in predicting severity early and treating adequately. 13 In contrast to our study, Turk Thorac J et al showed that NL ratio was lower (average NL=5.89) in COVID-19 positive SARI and was higher (avg NL=11.41) in non-COVID-19 SARI. 9 Regarding the association with co-morbidities, our study found that NL ratio was significantly higher in severe COVID-19 patients with diabetes and hypertension.…”
Section: Discussioncontrasting
confidence: 99%
“…12 A metanalysis done by Xiaoming et al to evaluate the predictive value of NL ratio suggested that NL ratio has good predictive in terms of severity and mortality in COVID-19 hence helping clinicians in predicting severity early and treating adequately. 13 In contrast to our study, Turk Thorac J et al showed that NL ratio was lower (average NL=5.89) in COVID-19 positive SARI and was higher (avg NL=11.41) in non-COVID-19 SARI. 9 Regarding the association with co-morbidities, our study found that NL ratio was significantly higher in severe COVID-19 patients with diabetes and hypertension.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the findings of Chan et al's 1 study were based on unadjusted effect estimates. Two other meta‐analyses on this topic also reported unadjusted effect estimates 2,3 . It was worth noting that a univariate analysis indicated that NLR was an important risk factor significantly associated with COVID‐19 severity.…”
Section: Author Country Cases (N) Age (Years) Male N (%) Study Design Outcomes Adjusted Effect Estimate (95% Ci) Confoundersmentioning
confidence: 99%
“…Several large studies of nonpregnant COVID-19 adults have shown that increased NLR has high degree of association with mortality and severe morbidity, with one study finding NLR to be the most important prognostic factor for severity. [6][7][8][9] This builds on prior evidence that the NLR is a highly sensitive predictor of prognosis in a wider spectrum of acute medical conditions such as brain infarct, cerebral hemorrhage, major cardiac events, and sepsis. [10][11][12][13] The studies investigating NLR in pregnant patients have been small.…”
mentioning
confidence: 90%